TSH receptor specific monoclonal autoantibody K1‐70TM targeting of the TSH receptor in subjects with Graves' disease and Graves' orbitopathy—Results from a phase I clinical trial. (6th February 2022) - Furmaniak, Jadwiga; Sanders, Jane; Sanders, Paul; Li, Yang; Rees Smith, Bernard
Abstract: Objectives: In Graves' disease (GD), autoantibodies to the thyroid stimulating hormone receptor (TSHR) cause hyperthyroidism. The condition is often associated with eye signs including proptosis, oedema, and diplopia (collectively termed Graves' orbitopathy [GO]). The safety profile of K1‐70 TM (a human monoclonal TSHR specific autoantibody, which blocks ligand binding and stimulation of the receptor) in patients with GD was evaluated in a phase I clinical trial. Patients and Study Design: Eighteen GD patients stable on antithyroid drug medication received a single intramuscular (IM) or intravenous (IV) dose of K1‐70 TM during an open label phase I ascending dose, safety, tolerability, pharmacokinetic and pharmacodynamic (PD) study. Immunogenic effects of K1‐70 TM were also determined. Results: K1‐70 TM was well‐tolerated in all subjects at all doses and no significant immunogenic response was observed. There were no deaths or serious adverse events. Increased systemic exposure to K1‐70 TM was observed following a change to IV dosing, indicating this was the correct dosage route. Expected PD effects occurred after a single IM dose of 25 mg or single IV dose of 50 mg or 150 mg with fT3, fT4, and TSH levels progressing into hypothyroid ranges. There were also clinically significant improvements in symptoms of both GD (reduced tremor, improved sleep, improved mental focus, reduced toilet urgency) and GO (reduced exophthalmos measurements, reduced photosensitivity). Conclusions: K1‐70 TM was safe, well tolerated and produced the expected PD effects with no immunogenic responses. It shows considerable promise as a new drug to block the actions of thyroid stimulators on the TSHR.